2016
DOI: 10.1038/cti.2016.57
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against CD80 in patients with COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is an inflammation disorder and possibly an autoimmune disease. The components of the autoimmune response in the circulatory system are of considerable interest to clinicians. Because aberrations of costimulation status have been noted in COPD, the presence of autoantibodies to B7 costimulatory factor CD80 were investigated in a cohort of patients. Recombinant rs1CD80 (lacking the transmembrane domain of CD80) was used for Western blot analysis and ELISA to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Previously, many autoantibodies such as anti-extracellular matrix proteins, anti-cytokeratins, anti-immune molecules antibodies have been suggested to associate with COPD and some of them have been shown to correlate with disease phenotypes, 19,22,[40][41][42][43] suggesting that those autoantibodies might contribute to the development of the disease. However, such associations have not been confirmed by others 45,[54][55][56][57] and were also not observed in our study using microarray data analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, many autoantibodies such as anti-extracellular matrix proteins, anti-cytokeratins, anti-immune molecules antibodies have been suggested to associate with COPD and some of them have been shown to correlate with disease phenotypes, 19,22,[40][41][42][43] suggesting that those autoantibodies might contribute to the development of the disease. However, such associations have not been confirmed by others 45,[54][55][56][57] and were also not observed in our study using microarray data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Since several autoantibodies including those against elastin, aggrecan, cytokeratin 18, cytokeratin 19, CD80, β2-microglobulin and collagen I, II and IV have already been suggested to be upregulated in COPD, 19,22,[40][41][42][43] we evaluated the expression of those autoantibodies in our samples. All those autoantigens were presented on the microarray, but no significant difference was observed for any of those autoantibodies between COPD patients and non-COPD smokers (Supplementary Table 3).…”
Section: Differentially Expressed Autoantibodies Between Copd Patientmentioning
confidence: 99%
“…Notably, according to this study, those autoantibodies are also present in inflammatory lung diseases suggesting that they are not COPD specific. Very recently, Luo et al investigated autoantibodies against a soluble form of CD80 (sCD80), a co-stimulatory molecule for T cell activation, in sera of patients with COPD ( 38 ). They found that serum levels of anti-sCD80 were higher in patients with COPD than in controls and were positively correlated to inflammatory cytokines, e.g., IL-6 and IL-8 ( 38 ).…”
Section: Autoantibodies In Copd Patientsmentioning
confidence: 99%
“…Very recently, Luo et al investigated autoantibodies against a soluble form of CD80 (sCD80), a co-stimulatory molecule for T cell activation, in sera of patients with COPD ( 38 ). They found that serum levels of anti-sCD80 were higher in patients with COPD than in controls and were positively correlated to inflammatory cytokines, e.g., IL-6 and IL-8 ( 38 ). Another immune molecule, β2-microglobulin that is a component of MHC class I molecules, has also been identified as an autoantigen in COPD ( 18 ).…”
Section: Autoantibodies In Copd Patientsmentioning
confidence: 99%
See 1 more Smart Citation